2020
DOI: 10.1042/bsr20190303
|View full text |Cite
|
Sign up to set email alerts
|

Identification of exosomal miR-455-5p and miR-1255a as therapeutic targets for breast cancer

Abstract: Accumulated evidence has demonstrated exosomes of cancer cells carry microRNAs (miRNAs) to non-malignant cells to induce metastasis. The present study aimed to identify crucial exosomal miRNAs for breast cancer (BC) using microarray data (GSE83669 and GSE50429) from Gene Expression Omnibus database, including exosomal samples from human BC cells (MCF7, MDA-MB-231) and normal mammary epithelial cell line (MCF10, MCF-10A), as well as original cell samples. Differentially expressed miRNAs (DEMs) were identified u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…For breast cancer, several miRNAs have been demonstrated to play roles in its progression. miR-455-5p and miR-1255a were upregulated with poor overall survival, while the overexpression of their target genes was related to a good overall survival, which indicated the potential roles of mir-455-5p and miR-1255a in the therapy of breast cancer [10]. miR-331 is upregulated in breast cancer, and it has been demonstrated to be dysregulated in many other cancers, such as lung cancer, gastric cancer, and prostate cancer [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 92%
“…For breast cancer, several miRNAs have been demonstrated to play roles in its progression. miR-455-5p and miR-1255a were upregulated with poor overall survival, while the overexpression of their target genes was related to a good overall survival, which indicated the potential roles of mir-455-5p and miR-1255a in the therapy of breast cancer [10]. miR-331 is upregulated in breast cancer, and it has been demonstrated to be dysregulated in many other cancers, such as lung cancer, gastric cancer, and prostate cancer [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 92%
“…Exosomes are vesicle-shaped structures with a diameter of 50–150 nm that can transport miRNAs as cargo. Various exosomal miRNAs have been identified in breast cancer such as exosomal miRNA-455-5p, -1255a, and -148a that can be used as therapeutic and diagnostic factors [ 110 , 111 ]. Exosomal miRNAs are capable of regulating PTEN expression in ensuring breast cancer malignancy.…”
Section: Microrna and Pten Relationshipmentioning
confidence: 99%
“…Accumulating evidence demonstrated that miRNAs play an important role in tumor growth and metastasis by regulating protein expression at the post-transcriptional level 42 . For instance, miR-455-5p is an high conserved miRNA and play critical roles in multiple tumors development and progression 25 , 27 , 32 - 35 , 39 , 43 . Yet, the expression profile and role of miR-455-5p in CCA development and progression remains largely unknown.…”
Section: Disscusionmentioning
confidence: 99%
“…Moreover, we demonstrated that PPP1R12A, a subunit of myosin phosphatase that play an critical role in regulating cell cycle and migration 25 , 34 , 39 , was a new direct target of miR-455-5p and PPP1R12A expression was negatively correlated with miR-455-5p in CCA tissues. Indeed, previous studies found that PPP1R12A interacted with insulin receptor substrate 1-insulin-like growth factor 1 receptor (IRS1-IGF1R) complex and mediated the process of IRS1 dephosphorylation, promoting PI3K/AKT cascade activation and in turn led to tumor cell proliferation and tumor growth 43 , 48 . In gastric cancer (GC) cells, silencing PPP1R12A inhibited GC cells proliferation by promoting cyclin D1 and c-myc expression to block the cell cycle 49 .…”
Section: Disscusionmentioning
confidence: 99%